Utilization of Microorganism-Based Biopesticides to Increase Crop Productivity - Gustian, Meko; Apriansi, Mardia; Raharjo , Randi; Erduansyah, Eki (Westscience Press, 2025)
The increased global emphasis on sustainable farming has accelerated interest in microorganism-based biopesticides as an alternative to chemical pesticides. This systematic literature review of 65 articles acquired from the Scopus database explains research trends, top journals, affiliations, and actual applications of microorganism-based biopesticides in increasing crop production. The results show a marked escalation in publications since 2018, with India, the United States, and Europe leading the research. Top journals such as Microorganisms for Sustainability and Crop Protection are essential for knowledge dissemination. Leading academic institutions, such as Banaras Hindu University, and governmental institutions, such as the USDA Agricultural Research Service, drive innovation in the field. This study chronicles the increasing global recognition of biopesticides as a contribution to sustainable agriculture and identifies the major areas requiring additional research, such as field efficacy, scalability, and regulation. These findings are valuable to policymakers, researchers, and agricultural stakeholders interested in introducing biopesticides into conventional farming systems.